Respuesta :

Answer: p = 13.9

Step-by-step explanation: 7(p-9) = 34.3 multiply 7 into p and -9

7p - 63 = 34.3  add 63 into both sides

7p = 97.3  divide 7 into both sides.

p = 13.9

This question can be solved in  two ways

the equation given is  7(p-9)=34.3

The first step to take is to divide both sides of the equation by 7

p - 9 = 34.3 / 7

p - 9 = 4.9

The second step is to combine similar terms

p = 4.9 + 9 = 13.9

A second method

the equation given is  7(p-9)=34.3

1. expand the bracket

7p - 63 = 34.3

2. Combine similar terms

7p = 34.3 + 63

7p = 97.3

3. Divide both sides of the equation by 7

p = 13.9

A similar question was solved here: https://brainly.com/question/20432589?referrer=searchResults